PERAN ANGGOTA DPRD KOTA GORONTALO PERIODE 2004-2009 DALAM PEMBUATAN PERATURAN DAERAH - Robby Hunawa (JURNAL LEGALITAS, 2010)
this research entitle \"role of council delegation of people area in making by law in city of gorontalo\".as according to research thiis research aim to know role of DPRD city of gorontalo in by law making in city of gorontalo,factors pursiung role of DPRD city of gorontalo in by law making in city of gorontalo and effords of DPRD city of gorontalo in overcoming factor pursiung role of DPRD city of methods research the used is descritipe method with inductive approach. population of this research is member of DPRD city of gorontalo ammouting to 40 people,while sample specified by using technique of smaples saturated pursuant to resulth of analisis hance cann be taken by conclusion:first,DPRD city of gorontalo not yet earnet to share in an optimal fashion in by law making in gorontalo in by law making in city in overcoming vaktors pursuing role of DPRD city of gorontalo in by law making in city of gorontalo pursuant to result of conclusion,writer givre sugestion that is:first,providing \"semiloka\" routinelly is,third specypik exprwesilly education of rock bottom council with tight selection band fifth council expected by more is voicing of importance of public,and is sixth,keeping ebtreast of and multiply of and also to be dialogued with siciety. Keyword: Role, Law, DPRD Gorontalo City.